High-Throughput Sequencing Analysis of the Changes in the Salivary Microbiota of Hungarian Young and Adult Subpopulation by an Anthocyanin Chewing Gum and Toothbrush Change - Boglárka Skopkó; Melinda Paholcsek; Anna Szilágyi-Rácz; Péter Fauszt; Péter Dávid; László Stündl; Judit Váradi; Renátó Kovács; Kinga Bágyi; Judit Remenyik (MDPI AG, 2023)
The sour cherry contains anthocyanins, which have bactericide action against some oral bacteria (Klebsiella pneumoniae, Pseudomonas aeruginosa). Sour cherry also has antibiofilm action against Streptococcus mutans, Candida albicans, and Fusobacterium nucleatum. Our earlier research proved that chewing sour cherry anthocyanin gum significantly reduces the amount of human salivary alpha-amylase and Streptococcus mutans levels. The microbiota of a toothbrush affects oral health and regular toothbrush change is recommended. A total of 20 healthy participants were selected for the study. We analysed saliva samples with 16S rRNA sequencing to investigate the effect of 2 weeks (daily three times, after main meals) of chewing sour cherry anthocyanin gum-supplemented by toothbrush change in half of our case-control study cohort-after scaling on human oral microbiota. A more stable and diverse microbiome could be observed after scaling by the anthocyanin gum. Significant differences between groups (NBR: not toothbrush changing; BR: toothbrush changing) were evaluated by log2 proportion analysis of the most abundant family and genera. The analysis showed that lower level of some Gram-negative anaerobic (Prevotella melaninogenica, Porphyromonas pasteri, Fusobacterium nucleatum subsp. vincentii) and Gram-positive (Rothia mucilaginosa) bacteria could be observed in the case group (BR), accompanied by build-up of health-associated Streptococcal network connections.